Homogeneous oxidation of C–H bonds with m-CPBA catalysed by a Co/Fe system: mechanistic insights from the point of view of the oxidant. Issue 1 (24th November 2021) - Nesterova, Oksana V.; Kuznetsov, Maxim L.; Pombeiro, Armando J. L.; Shul'pin, Georgiy B.; Nesterov, Dmytro S.
Abstract : A Co/Fe system efficiently catalyses the oxidation of C–H bonds with m -CPBA. The nitric acid promoter hampers the m -CPBA homolysis, suppressing the free radical activity. Experimental and computational data evidence a concerted oxidation mechanism. Abstract : Oxidations of C–H bonds with m -chloroperoxybenzoic acid ( m -CPBA) catalyzed by transition metal complexes are known to proceed through a number of routes, from the non-selective free radical to selective concerted and metal-mediated ones. However, there is a lack of understanding of the m -CPBA oxidative behavior, reaction mechanisms and factors that trigger its activity. An experimental and theoretical investigation of sp 3 C–H bond oxidation with m -CPBA in the presence of the heterometallic pre-catalyst [Co III 4 Fe III 2 O(Sae)8 ]·4DMF·H2 O (1 ) (H2 Sae = salicylidene-2-ethanolamine) and HNO3 promoter has been performed herein. The catalytic system 1 /HNO3 / m -CPBA allows mild hydroxylation of tertiary C–H bonds with 99% retention of stereoconfiguration of model alkane substrates, supported by high TOFs up to 2 s −1 (for cis -1, 2-dimethylcyclohexane) and TONs up to 1.4 × 10 4 (at 50 °C). The catalytic effect of 1 is seen at the ppm level, while 1000 ppm (0.1 mol%) loading allows 1000-fold increase of the initial reaction rate up to 9 × 10 −5 M s −1 . The reaction mechanism was investigated by means of combined kinetic studies (including isotope effects), isotopic labeling ( 18 O2, H2 18 O, D2 O), ESI-MS spectroscopy and DFT theoretical studies. The results suggest that the main oxidation pathway proceeds through a concerted mechanism involving a cobalt-peroxo C–H attacking species or via a cobalt–oxyl species (rebound process), rather than a free-radical pathway. Remarkably, the Co(iii ) catalyst does not change its oxidation state during the most energetically favored pathway, consistent with a metal–ligand cooperativity. The chlorobenzene radical is responsible for H abstraction in the non-selective side route, which is efficiently suppressed by the acidic promoter. Finally, signs for slow direct oxygen exchange between m -CPBA and water in the presence of a proton or a metal complex are found, suggesting that the results of 18 O-tests should be treated cautiously when m -CPBA is used as the oxidant.